2011
DOI: 10.1371/journal.pone.0016272
|View full text |Cite
|
Sign up to set email alerts
|

Social, Clinical and Microbiological Differential Characteristics of Tuberculosis among Immigrants in Spain

Abstract: BackgroundTo identify the differential tuberculosis (TB) characteristics within the immigrant population with respect to natives in Spain.Methodology/Principal FindingsA prospective cohort study design was implemented to examine the TB cases diagnosed and starting standard antituberculous treatment in Spain, between January 1st 2006 and March 31st 2007. A logistic regression analysis was performed to determine differential characteristics. 1,490 patients were included in the study population, 1,048 natives and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 14 publications
2
20
0
5
Order By: Relevance
“…8 Moreover, the percentage of foreign patients among the overall population of TB patients in Spain is 29.7%, according to a previous study, 12 and 35% according to our study, underlining the inadvisability and high risk of initiating 3drug treatment. This practice is clinically inacceptable, since the resistance rates in immigrant patients are known to be higher than in Spanish nationals (11.9% isoniazid resistance in immigrants, compared to 4.1% in nationals, according to a recent Spanish study).…”
Section: Discussionsupporting
confidence: 61%
“…8 Moreover, the percentage of foreign patients among the overall population of TB patients in Spain is 29.7%, according to a previous study, 12 and 35% according to our study, underlining the inadvisability and high risk of initiating 3drug treatment. This practice is clinically inacceptable, since the resistance rates in immigrant patients are known to be higher than in Spanish nationals (11.9% isoniazid resistance in immigrants, compared to 4.1% in nationals, according to a recent Spanish study).…”
Section: Discussionsupporting
confidence: 61%
“…The default rate in immigrants with TB in other study has been reported to be 11.5%13 and 19.5%14 depending on situations. To decrease default rate, political countermeasures such as strengthening emigration and immigration control and intensifying PPM collaboration by tracing TB medications of immigrants or directly observed treatment might be needed.…”
Section: Discussionmentioning
confidence: 76%
“…Poor nutrition, lack of fresh air, stress and hardships may also favor reactivation of remote infection followed by transmission under such conditions. Added to that drug resistance might promote subsequent clinical manifestations also [39,40]. Unfortunately contact tracing data were not available to further assess the hypothesis of local transmission within this specific study group, or within e.g.…”
Section: Discussionmentioning
confidence: 99%